Pengembangan Media Pembelajaran untuk Kompetensi Tata Bahasa pada Tingkat A1 bagi Siswa SMA - Enjel Muti Sitompul; Suci Pujiastuti (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to develop an interactive learning medium on the Gimkit platform with the topic of modal verbs at the A1 level. The research method applies a qualitative approach using the model of Richey & Klein (2017), which consists of three stages: (1) planning, (2) development, and (3) evaluation. The data source of this study is the book Grammatik aktiv A1–B1 by Friederike Jin and Ute Voß (2014), Chapter 5, pages 16–18, focusing on the topics: (1) conjugation of modal verbs in the present tense, (2) conjugation of modal verbs in the past tense, and (3) comparison of modal verbs in the present and past tenses. The learning medium was validated by a material expert with a score of 95 and by a media expert with a score of 90; both results fall into the category “very good.” Based on these results, the Gimkit learning medium on the topic of modal verbs is considered suitable and effective for teaching German at the A1 level in senior high schools, both for independent learning and for classroom instruction.